Gabapentin for post‐operative pain management – a systematic review with meta‐analyses and trial sequential analyses. Issue 9 (18th July 2016) - Fabritius, M. L.; Geisler, A.; Petersen, P. L.; Nikolajsen, L.; Hansen, M. S.; Kontinen, V.; Hamunen, K.; Dahl, J. B.; Wetterslev, J.; Mathiesen, O.
Abstract : Background: Perioperative pain treatment often consist of combinations of non‐opioid and opioid analgesics, 'multimodal analgesia', in which gabapentin is currently used. The aim was to document beneficial and harmful effects of perioperative gabapentin treatment. Methods: Randomized clinical trials comparing gabapentin vs. placebo or active placebo in adult surgical patients receiving gabapentin perioperatively were included. This review was conducted using Cochrane standards, trial sequential analysis (TSA), and Grading of Recommendations Assessment, Development, and Evaluation (GRADE). The primary outcomes were 24‐h opioid consumption and incidence of serious adverse events (SAE). Results: One hundred and thirty‐two trials with 9498 patients were included. Thirteen trials with low risk of bias reported a reduction in 24‐h opioid consumption of 3.1 mg [0.5, 5.6; TSA‐adjusted CI: −0.2, 6.3]. In the analysis of gabapentin as add‐on analgesic to another non‐opioid analgesic regimen, a mean reduction in 24‐h morphine consumption of 1.2 mg [−0.3, 2.6; TSA‐adjusted CI: −0.4, 2.8] in trials with low risk of bias was found. Nine trials with low risk of bias reported a risk ratio of SAEs of 1.61 [0.91; 2.86; TSA‐adjusted CI: 0.57, 4.57]. Conclusion: Based on GRADE assessment of the primary outcomes in trials with low risk of bias, the results are low or very low quality of evidence due to imprecision, inconsistency, and in some outcomes indirectness. Firm evidence for use of gabapentin is lacking as clinically relevant beneficial effect of gabapentin may be absent and harm is imminent, especially when added to multimodal analgesia.